PD-1/PD-L1 Based Combinational Cancer Therapy: Icing on the Cake - Zhang, Jian-ye; Yan, Yan-yan; Li, Jia-jun; Adhikari, Rameshwar; Fu, Li-wu (Frontiers in Pharmacology, 2020)
Cancer has been a major global health problem due to its high morbidity and mortality. While many chemotherapy agents have been studied and applied in clinical trials or in clinic, their application is limited due to its toxic side effects and poor tolerability. Monoclonal antibodies specific to the PD-1 and PD-L1 immune checkpoints have been approved for the treatment of various tumors. However, the application of PD-1/PD-L1 inhibitors remains suboptimal and thus another strategy comes in to our sight involving the combination of checkpoint inhibitors with other agents, enhancing the therapeutic efficacy. Various novel promising approaches are now in clinical trials, just as icing on the cake. This review summarizes relevant investigations on combinatorial therapeutics based on PD-1/PD-L1 inhibition.